OP0107 Teriparatide and Denosumab Combination Therapy and Skeletal Metabolism. (15th July 2016) - Fassio, A.; Gatti, D.; Viapiana, O.; Braga, V.; Idolazzi, L.; Adami, G.; Rossini, M.
Abstract : Background: Despite therapeutic options for osteoporosis have greatly expanded over the past few decades, the treatment of patients with established severe osteoporosis still remains challenging. Recently the combined teriparatide (TPD) and denosumab therapy was shown to increase bone mineral density (BMD) more than either agent alone. Objectives: The aim of this study was to compare the changes in bone turnover markers and in inhibitors of the Wnt canonical pathway in patients treated with either denosumab alone or TPD alone or when TPD was added to patients previously treated with denosumab. Methods: Open label prospective randomized study, involving 59 women over 65 years old affected by severe postmenopausal osteoporosis (with the evidence of at least two moderate-severe vertebral fractures), Bone turnover markers C-terminal telopeptide of type I collagen (CTX) and intact N-propeptide of type I collagen ad (P1NP) and inhibitors of the Wnt canonical pathway sclerostin (SOST) and Dickkopf-related protein 1 (DKK1) were evaluated. Results: In the groups treated with TPD or with denosumab alone bone turnover markers rose and decreased, respectively. In TPD group a later significant increase in DKK1 was observed, while in denosumab group a progressive increase in SOST was associated with a progressive significant decrease in DKK1. In the group treated first with denosumab and in which TPD was added 3 months later, the rounded values of both CTX and P1NP increased 3 months after the beginning of TPD by approximately the same absolute and percentage value of the group of patients treated with TPD alone, showing that the strong effect of denosumab on bone turnover is easily reversed by TPD treatment. In this group, SOST increased as in the denosumab alone group, while DKK1 progressively increased as in the TPD alone group. Conclusions: In conclusion, in this study we showed that TPD is able to express its biological activity even when bone turnover is fully suppressed by denosumab treatment. The combination therapy is associated with significant increases in both DKK1 and SOST, suggesting that the Wnt signalling pathway is not involved in the positive bone balance seen in the combination TPD-denosumab group. Disclosure of Interest: None declared